2021
DOI: 10.1186/s12876-021-01820-7
|View full text |Cite
|
Sign up to set email alerts
|

Somatization in patients with predominant diarrhoea irritable bowel syndrome: the role of the intestinal barrier function and integrity

Abstract: Background Irritable bowel syndrome (IBS) is characterised by gastrointestinal (GI) and psychological symptoms (e.g., depression, anxiety, and somatization). Depression and anxiety, but not somatization, have already been associated with altered intestinal barrier function, increased LPS, and dysbiosis. The study aimed to investigate the possible link between somatization and intestinal barrier in IBS with diarrhoea (IBS-D) patients. Methods Forty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
1
9
0
1
Order By: Relevance
“…Somatization, Interpersonal Sensitivity, Anxiety, and Psychoticism scores significantly reduced after diet, while Depression scores showed only a trend toward significance. These modifications refer essentially to those parameters mostly involved in the onset of IBS symptoms, especially in its diarrhea variant [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Somatization, Interpersonal Sensitivity, Anxiety, and Psychoticism scores significantly reduced after diet, while Depression scores showed only a trend toward significance. These modifications refer essentially to those parameters mostly involved in the onset of IBS symptoms, especially in its diarrhea variant [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The detection and measurement of skatole in urine were performed by a 3-methylindole kit (Eureka Lab Division, Chiaravalle, AN) using a high-performance liquid chromatography (HPLC) system (Thermo Fisher Scientific) as described previously by our group. 7 Urinary indole and skatole values higher than 20 mg l −1 and 20 μg l −1 are considered fermentative and putrefactive dysbiosis indices, respectively. 32 Lipopolysaccharide (LPS), a bacterial translocation marker, was assayed using an ELISA kit by Cloud-Clone Corp (Katy, TX, USA).…”
Section: Evaluation Of Indices Of Intestinal Dysbiosis Bacterial Tran...mentioning
confidence: 99%
“…We recently showed that IBS-D patients with high somatization scores suffered significantly more severe GI symptoms than patients without somatization. 7 This finding was associated with mild inflammation, dysbiosis, and impaired small intestinal permeability (s-IP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous TJ proteins have thus been found, such as cytoplasmic proteins zonula occludens-1 (ZO-1), the transmembrane proteins occluding and claudins ( Clark et al, 2006 ). The gut TJ barrier disruption leads to a “leaky” TJ barrier, resulting in a rise in gut permeability, and permitting paracellular permeation of luminal antigens that enhance intestinal inflammation, which is associated with various diseases comprising irritable bowel syndrome, diabetes, coeliac disease, non-alcoholic fatty liver disease, Crohn’s disease and so on ( Barbara et al, 2021 ; Portincasa et al, 2021 ; Prospero et al, 2021 ; Riedel et al, 2021 ; Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%